1956
DOI: 10.1073/pnas.42.11.841
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the Light Inhibition of Pea Stem Growth by the Gibberellins

Abstract: when inactive, denatured, virus RNA is incorporated into a reconstituted nucleoprotein. It should be emphasized that the present data do not, in our opinion, permit a choice between the foregoing alternative explanations. The possibility that small amounts of otherwise inactive virus RNA components may, when incorporated into DNA-bearing nucleoproteins, render the polymer infectious is subject to experimental verification. The same is true of the alternative proposal that TMV protein may induce some biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0

Year Published

1958
1958
1970
1970

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 6 publications
4
42
0
Order By: Relevance
“…Whether growth inhibition as a result of continuous low intensity irradiations is due exclusively to the red: far-red pigment system is not established. However, it is known that gibberellic acid may prevent stem growtlh inhibition as a result of 1)oth low and high initensity continuous irradiation in this species (1,4).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Whether growth inhibition as a result of continuous low intensity irradiations is due exclusively to the red: far-red pigment system is not established. However, it is known that gibberellic acid may prevent stem growtlh inhibition as a result of 1)oth low and high initensity continuous irradiation in this species (1,4).…”
Section: Discussionmentioning
confidence: 94%
“…Gibberellic acid treatment will prevent inhibition of pea stem growth by radiation (in both dwarf and tall varieties) and it will also reverse the dwarf character in peas as well as other species (1,4,8 2 a), but the promotions of growth are equal fractions of maximum growth promotion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lockhart (9,11) suggested that light regulates stem elongation in dwarf pea through some effect, or effects, on the metabolism of gibberellin. He Our experiments were aimed at finding whether stem growth due to gibberellin is controlled by the root system or stem and/or if an inhibitor is produced in the roots which may be translocated to the stem of the pea plant and in this way regulate stem growth.…”
mentioning
confidence: 99%